Espectroscopia Raman com pressão e baixas temperaturas em cristais de Cs2CuCl4 - Soares, Cássio César Silva (2022)
The Cesium tetrachlorocuprate, Cs2CuCl4, is a wide band gap semiconductor, with an orthorhombic structural shape (space group Pnma) and has been widely investigated for the phenomena that occur at low temperatures, such as, mainly, the emergence of a spin-liquid phase and antiferromagnetic transition due to Dzyaloshinsky-Moriya (DM) interactions. Although the knowledge of the electrical and magnetic properties at low temperatures of Cs2CuCl4 is a rich source for the physics of the material, the establishment of correlations between the structure and the vibrational properties is an important information, especially when it comes to of applications. In this context, this work consisted of the synthesis, characterization and analysis of vibrational properties by means of Raman spectroscopy of the compound Cs2CuCl4 as a function of temperature and hydrostatic pressure. The results confirmed the known orthorhombic structure in the Pnma space group and 22 active modes were found in Raman at a temperature of 12 K, with no apparent evidence of phase transition. Finally, investigations under hydrostatic pressure reveal possible phase transitions beyond that already reported.